The transnationalisation of the Indian coal economy and the Australian political economy: The fusion of regimes of accumulation?. (December 2016) - Rosewarne, Stuart
Abstract: The Indian government's economic development program is predicated on increasing electricity generating capacity. Coal fired power and removal of obstacles to private corporations investing in generating capacity are core elements in this program. With difficulties in boosting national coal production, the state-owned Coal India Limited and energy corporations have spearheaded a range of global coal sourcing endeavours, including investing in offshore deposits. Energy security has become reflected in engineering global supply chains, securing control of coal, with two of the largest projects involving Adani and GVK proposing to develop mines in the Galilee Basin in Queensland, Australia. These investments become the institutional and organisational architecture that locks in demand, a global demand which helps to explain successive Australian governments support for and approval of the projects. Notwithstanding considerable environmental opposition, and questions about the economic merits and commercial viability of the projects, Australian governments are wedded to the conviction that expanded development of the economy is tied to extracting and exporting fossil fuels, to consolidating Australia as an 'energy superpower'. Highlights: Expansion of India's electricity generation capacity is contingent on coal imports. Exporting coal is critical to Australia's ambitions as an energy superpower. The moral case for exporting coal is made in terms of poverty alleviation. Continued expansion of coal mining will compromise global climate change ambitions.